Métricas alimentarias de dos condrictios meso-bentónicos en aguas de Chile central - Canales-Cerro, Carlos; Morales, Naití A.; Concha, Francisco J.; Fernandoy, Francisco; Hernández, Sebastian; Meléndez, Roberto; Klarian, Sebastian A. (Revista de Biología Marina y Oceanografía, 2022)
Little has been studied of the food metrics of most chondrichthyans, which provide baseline information for the assessment of fishing status to guide the development of ecosystem-based management plans. Therefore, the main goal of this study was to approach the isotopic niche of Dipturus chilensis and Callorhinchus callorynchus in Valparaíso (central Chile). The main findings showed that C. callorynchus presented a narrow ellipse (E= 0.79; RC= 4.14; θ= 1.39), meanwhile D. chilensis, presented an ellipse with greater extension (E= 0.95; RC= 8,23; θ= -0.11), therefore a wide isotopic niche.